Aromatherapy with Lavender Oil to Reduce Pain Intensity in Post–Cesarean Section Patients: A Study at Cirebon Hospital - Kumalasari, Retno; Otis Putri Oktaviani, Pearly; Arieb Shintami, Rica; Rachmawati, Laily; Suyanti, Suyanti; Isnaeni, Siti (Media Publikasi Cendekia Indonesia, 2025)
Effective pain management after cesarean section (C-section) is critical for maternal recovery and well-being. Lavender aromatherapy has been suggested as a complementary therapy to reduce postoperative pain. This study aims to evaluate the effect of lavender aromatherapy on postoperative pain in women undergoing C-section. In a randomized, double-blind, placebo-controlled trial, 120 women undergoing C-section were assigned to either a lavender aromatherapy group (n=60) or a placebo group (n=60). Baseline characteristics, including age, education, parity, and smoking status, were assessed to ensure comparability. Postoperative pain intensity was measured using a standardized pain scale. Participants were predominantly aged 20–35 years (Placebo 91.67%, Aromatherapy 88.33%) and non-smokers. Educational attainment and parity were comparable between groups. Lavender aromatherapy significantly reduced post-C-section pain compared to placebo, The results showed a statistically significant difference in pain scores (U = 2638.5, p < 0.001, r = 0.40). The intervention was well-tolerated and easily applied, suggesting modulation of pain through both neurophysiological and psychological pathways. Lavender aromatherapy is a safe, non-invasive, and effective adjunct for postoperative pain management after C-section. Its integration into standard postoperative care may enhance maternal comfort and satisfaction. Further multicenter studies with standardized protocols are recommended to confirm efficacy and explore long-term outcomes